Effects of Green Tea Leaf Extract on Viability, Apoptosis, and Expression of Interleukin-6 in Keloid Fibroblasts - Fasihah, Mariah Shofwah; Hadi, Restu Syamsul; Mustofa, Samsul (Universitas Muhammadiyah Yogyakarta, 2024)
Green tea leaf (Camellia sinensis) extract contains polyphenols, anti-inflammatory and anti-carcinogenic agents that may effectively to as keloid therapy. This study aims to examine the effect of green tea leaf extract on viability, apoptosis, and interleukin-6 expression in keloid fibroblasts. Keloid fibroblast cultures were divided into groups that were cultivated with green tea extract at dosages of 100, 200, 400, and 800 μg/mL, negative control (10% Fetal Bovine Serum/FBS), and positive control (100 μM dexamethasone). This study used post-test-only control group design. The highest mean IL-6 expression was in the GTE 200 (275,942.7 pg/mL), while the lowest was in the GTE 800 ( -2,890.6 pg/mL). The viability and apoptosis was analized by using one-way ANOVA, continued with Least Significant Difference (LSD) with a significance of p 0.05 in the GTE 800 treatment group compared to the entire intervention group. Kruskal-Wallis followed by a Mann-Whitney was carried out for interleukin-6 (IL-6) with a significance of p 0.05 in the extract therapy group at dosages of 200, 400, 800 μg/ml and 100 μM dexamethasone. In conclusion, green tea leaf extract at 800 μg/ml could reduce viability interleukin-6 expression and increase apoptotic caspase-3 expression in keloid fibroblast cells.